IDENTIFICATION OF SOCIAL AND HEALTH POLICIES ON INFANT MORTALITY RATE IN KLATEN REGENCY - Sulistyowati, Ulfah; Ningsih, Yuliana Ristantya; Magna, Merlin Swantamalo (Sosiohumaniora, 2024)
Policy is a set of actions embodied as a product of laws to improve social interactions. Social and health policies are formulated to address public issues; for example, health issues upon which health policies are created to solve the respective issues. Infant mortality (IM) is one of the indicators used to assess the health prevalence and socioeconomic welfare of the community. Klaten, among other areas, suffers from high IM, so it is imperative to investigate this issue in Klaten Regency. The present study focuses on IM in Klaten Regency in 2020 and uses the Cluster Study to identify areas in Klaten Regency that need better attention and advocacy related to IM. This study aims to cluster the subdistricts in Klaten Regency based on IM variables, the number of pre-prosperous families, and the number of health facilities. In addition, this study investigates the obstacles to implementing the programs to reduce IM in Klaten Regencies. The results showed an unsatisfactory finding in all three variables. The Government Policy of Klaten Regency to reduce IM has been embodied in several flagship programs, such as SUKETI. However, the implementation of SUKETI Programs was not found in any publication, so it is considered not working. However, inequitable implementation of the programs due to the COVID-19 pandemic and other barriers has resulted in suboptimal, partial efforts to reduce IM.